Diabetes Self-Management Education on Dietary Compliance in Indonesia: A Descriptive Literature Review - Rompas, Meigi; Iswanti, Dwi Indah; Utama, Julvainda Eka Priya (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2024)
Diabetes Mellitus (DM) is a condition that is becoming more common worldwide, affecting both industrialized and developing countries. The objective of this study was to do a comprehensive analysis of the available literature in order to investigate the impact of Diabetes Self-Management Education (DSME) on adherence to dietary guidelines among individuals with diabetes in Indonesia. This study employed a method of descriptive literature review. Relevant keywords were used to conduct literature searches on academic databases including PubMed, Scopus, and Google Scholar. Relevant articles were picked based on specific criteria, and data were collected from them. The initial studies found from databases were 1,730 and after applied inclusion and exclusion criteria, the final studies included to this study was nine studies (2012 – 2024). The gathered data were subsequently examined through three distinct stages: data reduction, data presentation, and generating conclusions that was done by all authors. The results indicated that Diabetes Self-Management Education (DSME) programs had a notable effect on the degree of adherence to dietary guidelines in individuals with Diabetes Mellitus (DM). Patients who engaged in the DSME program exhibited greater adherence to the prescribed diet, in contrast to those who did not partake in the program.